Efektivitas Media Pembelajaran Digital pada Pembelajaran Matematika SMP - Isma Nurhasanah (REGRESI: Journal of Mathematics Education and Application, 2025)
Mathematics learning often faces problems such as students’ low conceptual understanding, motivation, and learning outcomes, mainly due to the abstract nature of the material and the continued use of conventional teaching methods. One alternative solution that has been widely studied is the use of digital-based learning media. This study aims to systematically analyze research findings related to the use of digital learning media in mathematics education. The method employed in this study is a Systematic Literature Review (SLR) by analyzing 12 relevant national journal articles. The articles were selected based on criteria including topic relevance, research methodology, and a focus on digital-based mathematics learning. The results of the review indicate that the use of digital learning media generally has a positive impact on mathematics learning, particularly in improving conceptual understanding, motivation, activeness, and learning outcomes of junior high school students. Digital media also help students visualize abstract mathematical concepts, making learning more meaningful. However, several challenges are still found in its implementation, such as limited infrastructure, teacher readiness, and access to technology. Based on these findings, it can be concluded that digital learning media have great potential to improve the quality of mathematics learning when supported by careful planning and teachers’ competence in utilizing educational technology..